The Noteworthy Reflections of Hypermasculinity in Sung Yu’s Master Teng-Tu - Gadi, Epifanius Karso Seda; Ibrahim, Laila Nabilahtuzzahro; Napitupulu, Johanes Claudio Perdana; Suyaji, Fransisca Irnidianis Magdalena; Pasopati, Rommel Utungga (Intertwine: Journal of English Language, Literary, and Cultural Studies, 2024)
This paper underlines matters of hypermasculinity in Sung Yu’s flash fiction entitled Master Teng-tu. This story tells about Sung-yu who is accused as an immoral man by the King. He asks help from Master Teng-tu then successfully escapes from the accusation concerning his morality. Through qualitative method and theory of hypermasculinity, the analysis of the story includes how the dialogues of Sung-yu and Master Teng-tu are matters of male superiority and underestimation to women. Sung-yu may win but his effort is not manly since he prioritizes himself more than the others. In conclusion, masculinity may always exist in society, but being a hyper version of it should be hindered. People should take care more of other people by concerning better moral considerations hereafter.